Imaging Recommendations for Diagnosis, Staging, and Management of Testicular Cancer - Katdare, Aparna; Popat, Palak; Sequeira, Rachel; Sable, Nilesh; Gala, Kunal; Chandra, Daksh; Agrawal, Archi; Prakash, Gagan; Murthy, Vedang; Menon, Santosh; Joshi, Amit; Singh, Ajaykumar; Kulkarni, Suyash (Indian Journal of Medical and Paediatric Oncology, 2023)
The common testicular tumors affect young males in the third and fourth decades and germ cell tumors especially have excellent post-treatment outcomes. Hence, guidelines for clinical, radiological, and tumor marker assessment for diagnosis, response assessment, and surveillance of these tumors have critical impact on the management of these tumors. This article aims to discuss the current recommendations and guidelines regarding the clinical and radiological assessment and treatment pathways of testicular tumors.
Keywords: guidelines; imaging; recommendations; testicular cancer